MFAP4 is a novel prognostic biomarker in glioma correlating with immunotherapy resistance and ferroptosis - Lv, Yuanhao; Gao, Ying; Di, Wenyu; Li, Zhaoyi; Shi, Yashen; Hou, Tianyuan; Chen, Yiyang; Tian, Jiaqi; Xu, Miaoming; Su, Wei; Zhang, Min; Zhong, Jiateng (Frontiers in Pharmacology, 2025)
BackgroundGlioma, an aggressive brain tumor, poses a challenge in understanding the mechanisms of treatment resistance, despite promising results from immunotherapy.MethodsGenes associated with immunotherapy resistance were identified by analyzing The Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA), and the Gene Expression Omnibus (GEO) database. In addition, gene set enrichment analysis (GSEA) was utilized to reveal relevant signaling pathways. Co-expression, differential expression and functional analyses were performed using TCGA-GBM/LGG, TIMER 2.0, MetScape, GTEx and LinkedOmics databases. Relationships with immune infiltration, ferroptosis and immune checkpoint genes were assessed. Gene mutations were explored by cBioPortal. Logistic regression, Lasso analysis, Receiver Operating Characteristic (ROC), Kaplan-Meier analysis, and Nomogram modeling assessed the correlation between MFAP4 and clinicopathological features of gliomas. By analyzing different datasets, we found that MFAP4 was aberrantly overexpressed in gliomas and correlated with poor clinicopathological features of gliomas. MFAP4 was an independent prognostic indicator and significantly correlated with glioma progression. We also performed functional and pathway enrichment analyses of MFAP4 in gliomas to explore its biological functions and potential molecular mechanisms in gliomas.ResultsMFAP4 was significantly elevated in glioma tissues compared to controls. MFAP4-related genes showed differential expression in pathways involving cytokines. Significant associations between MFAP4 levels, immune infiltration, ferroptosis, and immune checkpoint genes were found in glioma tissues. MFAP4 levels were correlated with glioma stage, histological type, and 1p/19q status, and independently predicted overall survival (OS), disease-specific survival (DSS) and progression-free interval (PFI). MFAP4 expression is effective in distinguishing tumor tissue from normal brain tissue. Furthermore, Spearman Correlation emphasizes the significant relationship between MFAP4 and ferroptosis-related genes.ConclusionOur study demonstrated that MFAP4 is aberrantly overexpressed in gliomas and correlates with adverse clinicopathological features. MFAP4 has relevance in regulating both tumor immunity and iron death, and cellular function assays have demonstrated that MFAP4 promotes the proliferation, migration, and invasion of glioma cells.